Technology For The Development Of Methodological Competencies Of Future Teachers Of Primary Education On The Basis Of Pedagogical Cooperation - Olimova Nodirabegim Ibroximjon qizi (Zien Journals, 2025)
This article explores the development of methodological competencies among future primary school teachers through the use of pedagogical collaboration. Methodological competence is understood as a teacher's ability to effectively plan, conduct, and evaluate lessons by applying modern teaching methods tailored to students’ age and individual characteristics. The study highlights the significance of cooperative learning environments, peer support, mentoring, and interactive teaching strategies in teacher education. The article is based on theoretical analysis, empirical observations, and synthesis of best practices. As a result, it proposes a structured technological approach for gradually developing methodological competencies in pre-service teachers within a framework of pedagogical partnership
Keywords: Future teacher; primary education; methodological competence